2007
DOI: 10.3354/meps07079
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of recruitment in a demersal fish as revealed by seabird diet

Abstract: Understanding recruitment in demersal fish requires determination of larval survival and delivery to appropriate settling habitats. Sanddabs Citharichthys sp. are an abundant neritic fish of Central California, an area of persistent upwelling. 'Upwelling shadows' develop in the lee of coastal promontories, retain surface waters, and may promote spatial variation in fish settlement. To test this hypothesis, we studied the diet and foraging dimensions of a seabird (Cepphus columba) specializing in sanddab consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
1
12
1
Order By: Relevance
“…We found a significant negative correlation between annual winter temperatures and annual spring and summer spawning for each year. In contrast, we found no relationship between annual interannual variability in upwelling could alter fish reproductive activity (Robinette et al 2007).…”
contrasting
confidence: 95%
See 2 more Smart Citations
“…We found a significant negative correlation between annual winter temperatures and annual spring and summer spawning for each year. In contrast, we found no relationship between annual interannual variability in upwelling could alter fish reproductive activity (Robinette et al 2007).…”
contrasting
confidence: 95%
“…We also found a significant positive relationship between annual spring upwelling and annual spring-summer fish egg abundance for each year, though additional sampling years are needed to adequately test this relationship. Similar to our study, Robinette et al (2007) found that more persistent annual spring upwelling led to increased larval abundance in central California.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…We investigated the breeding success of Common Murre ( Uria aalge ), Cassin's Auklet ( Ptychoramphus aleuticus ), Rhinoceros Auklet ( Cerorhinca monocerata ), Pigeon Guillemot ( Cepphus columba ), Brandt's Cormorant ( Phalacrocorax penicillatus ), and Pelagic Cormorant ( Phalacrocorax pelagicus ). All of these seabirds are pursuit‐diving species that select a variety of micronekton, including krill, and forage fish species such as juvenile rockfish, juvenile sanddab, and anchovy as prey for offspring provisioning (Ainley and Boekelheide 1990, Ainley et al 1996 a , b , Sydeman et al 1997, 2001, Robinette et al 2007; see Plate 1). Seabird breeding performance may be related to winter environmental conditions that occurred months before the initiation of breeding (e.g., egg lay date [Ainley and Boekelheide 1990, ]), but breeding success, measured as the number of young raised to fledging age, is largely a function of the parents ability to provision offspring during the chick‐rearing phase (Sydeman et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Most dietary studies of marine birds are restricted to the breeding season when birds are accessible on land and the prey loads of provisioning adults are observed or intercepted (Robinette et al 2007, Einoder 2009). Such colony-based information likely reflects the diets of chicks and should not necessarily be used to extrapolate adult diet (Williams et al 2007).…”
Section: Introductionmentioning
confidence: 99%